2019
DOI: 10.1590/0001-3765201920170928
|View full text |Cite
|
Sign up to set email alerts
|

Ecological aspects of natural populations of Hyalella pampeana (Crustacea, Amphipoda, Hyalellidae) from the Natural Reserve Island of Martín García (Río de La Plata, Argentina)

Abstract: Freshwater amphipods of the genus Hyalella have a great importance in aquatic ecosystems due to their role in matter and energy cycling and its utilization as bioindicators of environmental health. The aim of this work was to analyze relevant population parameters of Hyalella pampeana, such as population density and structure, individual body size, sex ratio, fecundity and recruitment, and to study the possible relation of these parameters to variations in environmental variables. Samples were taken monthly du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
3
5
1
2
Order By: Relevance
“…The positive correlation between the body size of ovigerous females and the number of eggs in the brood pouch in H. palmeirensis is similar to the results observed for H. azteca (Strong 1972;Othman & Pascoe 2001), H. pleoacuta e H. castroi (Castiglioni & Bond-Buckup 2007;Castiglioni & Bond-Buckup 2009), H. carstica (Torres et al 2015), H. gauchensis e H. georginae (Ozga et al 2017), H. bonariensis (Castiglioni et al 2018) and H. pampeana (Colla & César 2019). According to Castiglioni & Bond-Buckup (2009), body size of females may be related to the number of eggs produced, being that larger females are capable of producing more embryos and carry them in the brood pouch during the all embryonic development.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The positive correlation between the body size of ovigerous females and the number of eggs in the brood pouch in H. palmeirensis is similar to the results observed for H. azteca (Strong 1972;Othman & Pascoe 2001), H. pleoacuta e H. castroi (Castiglioni & Bond-Buckup 2007;Castiglioni & Bond-Buckup 2009), H. carstica (Torres et al 2015), H. gauchensis e H. georginae (Ozga et al 2017), H. bonariensis (Castiglioni et al 2018) and H. pampeana (Colla & César 2019). According to Castiglioni & Bond-Buckup (2009), body size of females may be related to the number of eggs produced, being that larger females are capable of producing more embryos and carry them in the brood pouch during the all embryonic development.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, it was observed that H. palmeirensis adheres to macrophyte roots, with abundance peak occurring from spring to summer (October to January), season where there also a high abundance of macrophytes. Colla & César (2019) reported similar results in H. pampeana where amphipods increased their numbers together with the macrophyte development in warmers months. Aquatic vegetation cover is an important factor influencing invertebrate community structure, presumably because the vegetation creates structural heterogeneity and it can provide refuges and food resources (Hargrave 1970;Waterkeyn et al 2008).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Hyalella curvispina has varied feeding habits: shredder, predator, scrapper, and collector-collector (Cummins et al 2005;Giorgi and Tiraboschi 1999;Saigo et al 2009;Wantzen and Wagner 2006). They are also food for other macroinvertebrates, fish, amphibians, and birds (Colla and César 2019). As a defense mechanism against predation pressure, Hyalella species occupy different habitats (Wellborn 1995).…”
Section: General Considerationsmentioning
confidence: 99%
“…Las características ambientales de cada microhábitat acuático son importantes para el establecimiento y persistencia de sus poblaciones. Por ejemplo, el pH influye en la densidad de estos (Colla & César, 2019).…”
Section: Orden Anfipodaunclassified